The study of pro as an empty category in Azeri Turkish language - Nezhad, Mohammad Reza Pahlavan; Habibi, Mozhghan (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This paper examines the pro-drop parameter in Azeri Turkish. First, some basic concepts and theories in terms of Chomsky’s generative grammar school and principles and parameters theory are introduced. Then some theoretical background on the subject of Persian and Turkish languages are briefly presented. Next part is about explanation and description of pro features and some evidence and samples of Italian and Persian and Azeri Turkish languages and the last section deals with the results of this study. After giving and comparing evidence of these three languages we conclude that is that Azeri Turkish is a pro-drop language which allows subject to drop and establishes pro as a null subject (an empty category) in the position of subject and object can also be removed in some instances and proarb is established in the position of object.